2013
DOI: 10.1038/srep01441
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Diffraction Barrier Using Fluorescence Emission Difference Microscopy

Abstract: We propose a novel physical mechanism for breaking the diffraction barrier in the far field. Termed fluorescence emission difference microscopy (FED), our approach is based on the intensity difference between two differently acquired images. When fluorescence saturation is applied, the resolving ability of FED can be further enhanced. A detailed theoretical analysis and a series of simulation tests are performed. The validity of FED in practical use is demonstrated by experiments on fluorescent nanoparticles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
103
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(104 citation statements)
references
References 25 publications
0
103
0
1
Order By: Relevance
“…Yet, the SNR required for measuring a cubic 300 nm alkane domains with the differential scheme presented here is thus of the order of 10 −4 -10 −5 (i.e., for a magnitude a decade above noise level). Since earlier works have highlighted that subtraction-based imaging are more noise-sensitive than schemes where imaging is achieve with a single measure [37][38][39][40][41], and that this may impact on the experimental resolution [40], it remains important to compare the SNR requirements of the differential absorption scheme with past experimental achievements in absorption spectroscopy and microscopy. Variations in transmission of the order of 10 −4 were recorded in a pump-probe absorption microscopy scheme [63] and a SNR of 16:1 rms was achieved when detecting IR absorption in a Fourier transform setup with a reference beam 10 4 more intense than the signal beam [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the SNR required for measuring a cubic 300 nm alkane domains with the differential scheme presented here is thus of the order of 10 −4 -10 −5 (i.e., for a magnitude a decade above noise level). Since earlier works have highlighted that subtraction-based imaging are more noise-sensitive than schemes where imaging is achieve with a single measure [37][38][39][40][41], and that this may impact on the experimental resolution [40], it remains important to compare the SNR requirements of the differential absorption scheme with past experimental achievements in absorption spectroscopy and microscopy. Variations in transmission of the order of 10 −4 were recorded in a pump-probe absorption microscopy scheme [63] and a SNR of 16:1 rms was achieved when detecting IR absorption in a Fourier transform setup with a reference beam 10 4 more intense than the signal beam [21].…”
Section: Resultsmentioning
confidence: 99%
“…These include reversible optical fluorescence transition (RESOLFT) microscopies such as for example stimulated emission depletion (STED) microscopy [25-32], non-linear saturated structured illumination microscopy (SSIM) [33,34], and single molecule localization microscopies such as stochastic optical reconstruction microscopy (STORM) [35,36]. Several image subtraction methods have also been developed to improve the lateral resolution of fluorescence confocal microscopy, using different detection pinhole geometry [37-39] or vortex-shaped illumination [40,41]. However, all these methods generally require the introduction of fluorescent markers in the samples which are the species that is truly measured in the samples.…”
Section: Introductionmentioning
confidence: 99%
“…According to the concept of FED, 14 two confocal images are generated and then go through a subtraction process. One image is illuminated by a solid focal spot, hence it is an ordinary confocal image.…”
Section: B Fluorescence Emission Difference Microscopymentioning
confidence: 99%
“…Previous researches have shown that the subtraction of confocal images taken under different pinhole sizes can improve the resolution, 12,13 but the signal-to-noise ratio is relatively low. Recently, a better subtraction method named fluorescence emission difference microscopy (FED) 14 is proposed. Similar methods include switching laser mode microscopy (SLAM) 15,16 and a approach based on ground state depletion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation